Students’ Perception Towards Method Used By The Teacher In Teaching English - Mans Lapanda; Vivin Krismawanti Modjanggo (Sintuwu Maroso Journal of English Teaching, 2023)
This research is carried out is to find out students’ perception of teacher’s method in teaching English at the second grade students of SMP N 1 Lore Selatan. The researcher uses descriptive quantitative research. The population of this research is the second grade students of SMP N 1 Lore Selatan, academic year of 2021/2022 that consists of 96 students. The sample of this research is 35 students who are selected by using purposive sampling technique. Questionnaire is used to collect the data which is delivered by using Google Form media. The result of the research shows that the second grade students of SMP N 1 Lore Selatan academic year of 2021/2022 have good perception toward English teacher’s method in teaching English. It can be seen from students’ perception toward English teacher method in visual aspect is 74,04% and categorized good, students’ perception toward English teacher method in verbal aspect is 80,38% and categorized good, and students’ perception toward English teacher method in relation aspect is 79,43% and categorized good.